From Crisis to Enlivenment: An AOM President Responds to EO13769. (July 2019) - Pirson, Michael A.; Adler, Paul S.; Barney, Jay B.; Bartunek, Jean M.; Patient, David L.; Phillips, Nelson; Pitelis, Christos N.; Walsh, James P.
In assembly of short responses, noted scholars—including former presidents of the Academy of Management (AOM)—share their perspectives on the events related to AOM leadership following EO13769. The pieces are reflections on the micro-level aspects of leadership and the ethical and moral choices therein.